PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV SD NEGERI 241 PALEMBANG (JS (JURNAL SEKOLAH), 2021)
Abstract: Application Of Cooperative Learning Model Type Of DiscoveryLearning In Increasing Science Learning Outcomes In Class IV Students SDNegeri 241 Palembang. The purpose of this action research is to determine theincrease in student learning outcomes after the implementation of the DiscoveryLearning Type Cooperative Learning Model. This study uses two rounds of actionresearch (classroom action research). Each round consists of four stages, namely:design, activities and observations, reflection, and revision. The location of thisclassroom action research was carried out at SD Negeri 241 Palembang, SouthSumatra province. This research was conducted from February to April 2019 forthe 2018/2019 academic year. The subjects of this study were students of classIV.A SD Negeri 241 Palembang, totaling 30 students. The main topic ofdiscussion was about the material "Energy and Its Use". The data obtained were inthe form of formative test results, observation sheets for teaching and learningactivities and documentation. From the results of the analysis, it was found that thelearning outcomes of students experienced a significant increase marked by anincrease in students' learning mastery in each cycle, namely pre-cycle (21.88%),cycle I (66.67%) and (86.67%) in cycle II. The conclusion of this study is that thecooperative learning model of the Discovery Learning type can have a positiveeffect on the learning outcomes of students at SD Negeri 241 Palembang, and thislearning model can be used as an alternative in efforts to improve science learning.Keywords: Learning Outcomes, cooperative learning model typeDiscovery Learning, IPAAbstrak: Penerapan Model Pembelajaran Kooperatif Tipe DiscoveryLearning Dalam Meningkatkan Hasil Belajar IPA Pada Siswa Kelas IV SDNegeri 241 Palembang. Tujuan dari penelitian tindakan ini adalah untukmengetahui peningkatan hasil belajar peserta didik setelah diterapkannya ModelPembelajaran Kooperatif Tipe Discovery Learning. Penelitian ini menggunakanpenelitian tindakan (classroom action research) sebanyak dua putaran. Setiapputaran terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan,refleksi, dan revisi. Lokasi penelitian tindakan kelas ini dilaksanakan di SD Negeri241 Palembang, provinsi Sumatera Selatan. Penelitian ini dilaksanakan padaFebruari s/d April 2019.Subjek penelitian ini adalah peserta didik kelas IV.A SDNegeri 241 Palembang yang berjumlah 30 peserta didik. Pokok bahasan yangdisampaikan mengenai materi œEnergi dan Penggunaannya.Data yang diperolehberupa hasil tes formatif, lembar observasi kegiatan belajar mengajar dandokumentasi. Dari hasil analis didapatkan bahwa hasil belajar peserta didikmengalami peningkatan yang signifikan ditandai dengan peningkatan ketuntasanbelajar peserta didik dalam setiap siklusnya, yaitu pra siklus (21.88 %),siklus I(66.67%) dan (86.67%) pada siklus II. Kesimpulan dari penelitian ini adalahmodel pembelajaran kooperatif tipe Discovery Learning dapat berpengaruh positifterhadap hasil belajar peserta didik SD Negeri 241 Palembang, serta modelpembelajaran ini dapat digunakan sebagai salah satu alternatif dalam upayaperbaikan pembelajaran IPA.Kata Kunci: Hasil Belajar, model pembelajaran kooperatif tipeDiscovery Learning, IPA